2006
DOI: 10.1039/b514826j
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spectroscopy of the Ã1A″← X̃1A′ system of CDF

Abstract: To further investigate the Renner-Teller (RT) effect and barriers to linearity and dissociation in the simplest singlet carbene, we recorded fluorescence excitation spectra of bands involving the pure bending levels 2(n)(0) with n = 0-9 and the combination states 1(1)(0)2(n)(0) with n = 1-8 and 2(n)(0)3(1)(0) with n = 0-5 in the A(1)A''<-- X(1)A' system of CDF, in addition to some weak hot bands. The spectra were measured under jet-cooled conditions using a pulsed discharge source, and rotationally analyzed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 70 publications
2
25
0
Order By: Relevance
“…NiI was produced using a pulsed discharge source, wherein Ni atoms sputtered from stainless steel electrodes (Type 303 stainless contains 8-10% Ni) reacted with an appropriate iodine-containing precursor seeded in $3 bar Ar (Airgas). Consistent with our previous study of CuOH using a similar source [20], a rotational temperature in the range of 50 K was determined from preliminary fits of 0009-2614/$ -see front matter Ó 2010 Elsevier B.V. All rights reserved. doi:10.1016/j.cplett.2010.08.016 the fluorescence excitation spectra [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NiI was produced using a pulsed discharge source, wherein Ni atoms sputtered from stainless steel electrodes (Type 303 stainless contains 8-10% Ni) reacted with an appropriate iodine-containing precursor seeded in $3 bar Ar (Airgas). Consistent with our previous study of CuOH using a similar source [20], a rotational temperature in the range of 50 K was determined from preliminary fits of 0009-2614/$ -see front matter Ó 2010 Elsevier B.V. All rights reserved. doi:10.1016/j.cplett.2010.08.016 the fluorescence excitation spectra [21].…”
Section: Methodsmentioning
confidence: 99%
“…The unfocussed laser beam crossed the molecular beam 10 mm downstream, and the resulting fluorescence was collected by a two lens f/2.4 assembly and filtered via a combination of long-pass and short-pass cutoff filters (Corion or Edmund Scientific) prior to detection by a photomultiplier tube detector (Oriel) held at $À1000 V. Emission spectra were obtained using a 0.3 m spectrograph (Action SR303i with ISTAR CCD) in photon counting mode, typically with a 160 lm slit width and integration over 15,000 laser shots, and were calibrated using the output of an Fe:Ne hollow cathode lamp (Photron). Bands in the emission spectra were fit to a Gaussian line shape function, using Origin 7.5 software; previous studies have shown the validity of this approach [19][20][21]. The uncertainty in the derived band positions is ±2 cm À1 .…”
Section: Methodsmentioning
confidence: 99%
“…The apparatus, pulsed discharge nozzle, and data acquisition procedures are identical to those used in previous studies of CHF, CDF, CHBr, CDBr, and CHCl [8,[44][45][46][47][48][49][50][51][52][53][54], and, therefore, only the important differences will be highlighted. The carbene CDCl was produced using a pulsed electrical discharge through a $1-2% mixture of CD 2 Cl 2 (Cambridge Isotope Labs, 99.9 atom % of D) seeded in high purity He.…”
Section: Methodsmentioning
confidence: 99%
“…Most recently, we reported comprehensive surveys of theà 1 A 00 X 1 A 0 system of CHBr, CDBr, and CHCl using fluorescence excitation and single vibronic level (SVL) emission spectroscopy [8,53,54]. In each case we recorded and analyzed many new cold bands, and reported the first measurement of theà 1 A 00 state C-H stretching frequencies following the observation of bands in the progressions 1 1 0 2 n 0 and 1 1 0 2 n 0 3 m 0 [36,46,52]. Exploiting these as pump transitions in SVL emission spectroscopy, we examined the vibrational level structure up to $9000 cm À1 above the vibronic origin ofX 1 A 0 , reporting many previously unobserved levels in both theX 1 A 0 and a 3 A 00 states and probing spin-orbit mixing in these systems in new detail.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation